Diversidade química, genética e estudo do potencial formicida de óleos essenciais de Eplingiella fruticosa (Salzm. Ex Benth) Harley & J.F.B. Pastore - Silva, Dennis Crystian (2017)
Eplingiella fruticosa Salzm. ex Benth., ex Hyptis fruticosa is a shrubby plant of the family Lamiaceae, found mainly on the coast of northeastern Brazil. This study aimed to characterize the chemical and genetic properties of the essential oil of E. fruticosa native to the state of Sergipe. Native populations were collected in 11 municipalities in the state of Sergipe. The essential oils from dry leaves were collected by hydrodistillation and analyzed by GC/MSFID. The mean essential oil content ranged between 0.75 and 1.28%. The chemical and clustering analysis of the essential oils revealed two clusters, based on the higher contents of constituents. The first cluster consisted of 15 plants and had bicyclogermacrene (6.29- 16.24%), spathulenol (7.59-15.23%), β-caryophyllene (5.77-12.97 %), and caryophyllene oxide (5.00-11.90%) as major constituents. The second cluster consisted of seven plants and had 1,8-cineol (8.96-15.51%), α-pinene (5.46-13.77%), and camphor (4,08-11.40%) as major constituents. The analysis of genetic diversity by ISSR comprised samples of 100 plants and used eight primers. Results of the clustering analysis by the Neighbor-Joining method formed three clusters: Cluster I, consisting of 50 plants, mainly from the municipalities of Areia Branca, Estância, Japaratuba, Moita Bonita, Pirambu, and Salgado; Cluster II, formed by 21 plants, nine representatives of the municipality of Itaporanga D'Ajuda and 13 representatives of other municipalities; Group III, made up of 29 plants, mainly from the municipalities of Malhada dos Bois and São Cristóvão. The lowest genetic distance was observed between plants EPF94 and EPF96 (0.250), and the highest genetic distance was observed between plants EPF50 and EPF96 (0.9778). The Shannon index presented a mean value of 0.42, and diversity was considered as moderate. Heterozygosity reached a mean value of 0.267 and was considered as low. The polymorphic information content (PIC = 0.253) was considered as moderately informative. The essential oils of four E. fruticosa genotypes were toxic to workers of Acromyrmex balzani, requiring 4.54-6.78 μL.L-1 of oil to cause 50% mortality of the ants. When applied alone, camphor and 1,8-cineol were more effective than the essential oil; conversely, β-caryophyllene and caryophyllene oxide were less toxic. Treatments reduced the survival rate of A. balzani throughout the exposure time, especially the essential oils of the genotypes EPF303 and EPF1103 and their respective constituents isolated, which presented the shortest lethal times. The treatments affected the ants' behavior, confirming the repellency of the essential oils tested in this study. Results revealed the existence of chemical variability among E. fruticosa plants of the state of Sergipe and intermediate genetic diversity among plants. The essential oils and the constituents isolated have the potential for the development of effective products to control leaf-cutting ants.